A Review of Potency of Cassava Peel Waste and Seaweed Carrageenan as Environmentally Friendly Bioplastic - Esa Ghanim Fadhallah; Nana Juwita; Indah Nurul Assa'diyah; Sholeha Tullaila; Shaffa Audya Nurin Putri; Rian Adi Prayoga; Bella Amanda Iswahyudi (CV FOUNDAE, 2022)
Plastic waste continues to increase every year along with the increasing number of industries and population. Accumulated plastic waste has a negative impact and harm the environmental. The initiative of 3R (reduce, reuse, and recycle) has been widely promoted, but it is not optimally implemented. The use of organic materials to substitute the synthetic materials in plastic become alternative to prevent this problem continues in the future. Bioplastics are naturally decomposed by the soil and made from renewable materials. This review aims to explore the potency of cassava peels (Manihot esculenta) and seaweed carrageenan (Eucheuma cottonii) as the bioplastic material. The method used is an effective literature review and in accordance with the topic being discussed. The discussion method is carried out based on research results that have been found by previous researchers, which are then integrated with other researchers to get strong results and conclusions. Cassava peel waste and seaweed carrageenan have the potency to be made into bioplastics because they contain polysaccharide that can form a thin layer films based on gelatinization. The development of cassava peel waste and seaweed carrageenan will becoming the promising materials as substitutions for synthetic plastic, and also could help prevent the negative impact of plastic waste. Furthermore, since the cassava and seaweed are naturally abundant, it will promoting the environmental sustainability.